2021
DOI: 10.1111/apa.16116
|View full text |Cite
|
Sign up to set email alerts
|

Very preterm infants admitted to a tertiary neonatal unit in central Vietnam showed poor postnatal growth

Abstract: Premature birth and its complications are major challenges for global healthcare. An estimated 5.3 million children under five years of age died in 2018, and complications from preterm birth accounted for 18% of these deaths. 1 There are an estimated 15 million babies born prematurely each year, comprising 11% of all births (range 5%-18%). 2 In 65 countries with reliable data, there has been an increase in premature births over the past two decades.Preterm infants have a higher mortality rate than term infants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Recently, Rochow et al 3 showed that z‐score alone may not be a good indicator of postnatal growth and suggested using weight gain ratio. The other reassuring observation noted in the study of Tran et al 1 was a low incidence of small for gestational age infants in their cohort (3.8%, 3/78). The US SGA births in 2009 and 2010 were reported to be around 10% 4 …”
mentioning
confidence: 50%
See 2 more Smart Citations
“…Recently, Rochow et al 3 showed that z‐score alone may not be a good indicator of postnatal growth and suggested using weight gain ratio. The other reassuring observation noted in the study of Tran et al 1 was a low incidence of small for gestational age infants in their cohort (3.8%, 3/78). The US SGA births in 2009 and 2010 were reported to be around 10% 4 …”
mentioning
confidence: 50%
“…In conclusion, the study by Tran et al 1 is impressive, but I think looking at the average GV of the cohort, we should not label the infants to have poor growth just based on z‐score alone.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…The numbers (percentages) of males and the histories of antenatal steroid administration were: 317 neonates (57.1%) and 423 neonates (76.2%), respectively. The median (IQR) GA and BW were 29 (27)(28)(29)(30)(31) weeks and 1180 (860-1475) grams, respectively. The lowest GA and BW were 22 weeks and 410 grams, respectively.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…We thank Dr Manzar for his interest in our publication 1 and his interesting comments 2 . He suggested that defining poor growth in very preterm infants should not be based on z ‐scores alone.…”
mentioning
confidence: 99%